Mobile phone use for agribusiness by farmers in Southwest Nigeria (2016)
This study investigated how farmers in Southwest Nigeria use mobile phones for agribusiness, the benefits of the use of mobile phones, and the challenges farmers face using the device. Driven by theory of information and communication technology for development, this study adopted survey and focus group discussion (FGD) methods. Stratified, random, purposive and convenience sampling techniques were employed to select the sample. A questionnaire and FGD guide were used to collect data. Findings revealed that, among all the mobile phone features, the mostly used feature by farmers is radio at the rate of 75.9%, while the mostly deployed phone service is voice call (83.4%). Mobile phone use contribute to increase in farmers’ income, reduction in transaction and transportation costs, and increase in farm productivity. However, epileptic electricity supply hinders the effective use of mobile phones for agribusiness. Infrastructural facilities, especially electricity, should be provided in the rural areas to enable farmers use mobile phones effectively for agribusiness activities and ensure sustainable agricultural development.